2018
DOI: 10.1016/j.trim.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Elevated intragraft expression of innate immunity and cell death-related markers is a risk factor for adverse graft outcome

Abstract: Complement- and apoptosis-related gene expression is elevated in deceased donor transplants before transplantation. High BAX:BCL2 ratio and TLR4 expression during AR may reflect enhanced intragraft cell death and immunogenic danger signals, and pose a risk factor for adverse graft outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Additionally, the majority of predictive transcriptomic studies in KT have focused on DGF as a surrogate marker, without being able to predict longer-term outcomes (>12 months). 27,28,[30][31][32][33][34][35] We found that DGF was not significantly associated with 24-month function (p = .238), explaining why gene sets associated with DGF have poor predictive value. 8,36 Furthermore, most transcriptomic studies have utilized postreperfusion biopsies, which are less likely to capture intrinsic organ quality due to the "transcriptional noise" induced by reperfusion injury, surgical procedures, recipient immune infiltration, and immunosuppressive medications.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Additionally, the majority of predictive transcriptomic studies in KT have focused on DGF as a surrogate marker, without being able to predict longer-term outcomes (>12 months). 27,28,[30][31][32][33][34][35] We found that DGF was not significantly associated with 24-month function (p = .238), explaining why gene sets associated with DGF have poor predictive value. 8,36 Furthermore, most transcriptomic studies have utilized postreperfusion biopsies, which are less likely to capture intrinsic organ quality due to the "transcriptional noise" induced by reperfusion injury, surgical procedures, recipient immune infiltration, and immunosuppressive medications.…”
Section: Discussionmentioning
confidence: 70%
“…Thus far, a limited number of peer-reviewed pretransplant kidney GE studies have been conducted in the field. [25][26][27][28][29][30][31][32][33] Of these studies, only two evaluated graft outcomes beyond 1 year (both of which had small sample sizes and used targeted gene approaches). 29,33 Critically, none of the previous studies included external validations, which are necessary to determine the reproducibility and generalizability of results in different patient populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCL2 (BCL2 Apoptosis Regulator) is an anti-apoptotic protein that prevents the death of specific cells like lymphocytes. The expression of BCL2 may reflect the enhancement of cell death and immunogenicity risk signals in transplantation and constitute a risk factor for poor transplantation results ( 31 ). Further, HSPA4 is expressed in heat resistance, damage signaling molecules (DAMPs), and ICD ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible reason is that AKI can induce the activation of innate immune system. After transplant, it can be a crosstalk to the activation of allograft rejection [28][29][30] . Taken together, the main reason of the adverse allograft outcome in AKI-elderly-DDKT subgroup might be the low nephron mass at baseline.…”
Section: Discussionmentioning
confidence: 99%